In‐utero coxsackievirus B4 infection of the mouse thymus. (29th November 2016) - Jaïdane, H.; Halouani, A.; Jmii, H.; Elmastour, F.; Abdelkefi, S.; Bodart, G.; Michaux, H.; Chakroun, T.; Sane, F.; Mokni, M.; Geenen, V.; Hober, D.; et al.
Summary: Type B coxsackievirus (CV‐B) infections are involved frequently in the triggering of several autoimmune diseases such as myocarditis, dilated cardiomyopathy, pericarditis, pancreatitis, type 1 diabetes, encephalitis, thyroiditis or Sjögren's syndrome. Serological and virological evidence suggests that maternal infections during pregnancy can play a role in the appearance of these diseases in offspring. The current study aims to explore the effect of an in‐utero CV‐B infection on the fetal thymus, the central site for programming immunological self‐tolerance. In this perspective, female Swiss albino mice were inoculated intraperitoneally or orally with the diabetogenic CV‐B4 E2 strain at gestational days 10 or 17. Offspring were killed at different post‐inoculation times, and their thymuses were analysed for evidence of infection and alterations in thymic T cell subsets. In‐utero CV‐B infection of the thymus was demonstrated during the course of vertical transmission, as attested by viral RNA and infectious virus detection in most analysed samples. No histopathological changes were evident. Thymic T cells were not depleted, despite being positive for viral RNA. As evidenced by flow cytometry analysis, CV‐B infection of the fetal thymus induced significant changes of thymic T cell populations, particularly with maternal inoculation at gestational day 10. Altogether, these findings suggest that CV‐B infection of the fetal thymus may play an important role in the genesis of autoimmune diseases. Abstract : Fetal thymus infection is thought to be one of the pathophysiological mechanims linking type B coxsackievirus infections to the genesis of associated autoimmune diseases like type 1 diabetes. To explore this hypothesis we used an outbred mouse model in which pregnant dams were inoculated by the diabetogenic CV‐B4 E2 strain at either gestational day 10 or 17, and by either the intraperitoneal or the oral route. Regardless of the inoculation route and period, virus transmission to offspring's thymuses could be evidenced without structural damage of that organ, but significant anomalies in the different T‐cell subsets were observed.